Hegel and the metaphysics of absolute negativity - Bowman, Brady (Modern European philosophy., 2013)
"Hegel's doctrines of absolute negativity and 'the Concept' are among his most original contributions to philosophy and they constitute the systematic core of dialectical thought. Brady Bowman explores the interrelations between these doctrines, their implications for Hegel's critical understanding of classical logic and ontology, natural science and mathematics as forms of 'finite cognition', and their role in developing a positive, 'speculative' account of consciousness and its place in nature. As a means to this end, Bowman also re-examines Hegel's relations to Kant and pre-Kantian rationalism, and to key post-Kantian figures such as Jacobi, Fichte and Schelling. His book draws from the breadth of Hegel's writings to affirm a robustly metaphysical reading of the Hegelian project, and will be of great interest to students of Hegel and of German Idealism more generally"--